Consumers’ Intention toward Mitigation of Plate Waste Behaviour in Restaurants – Development of Conceptual Model - Meghana Salins; Aithal P. S., (International Journal of Management, Technology and Social Sciences (IJMTS), 2023)
Purpose: There have been growing concerns over food security and the problems of food waste on the environment, including resource depletion and greenhouse gas emissions for many years. Although food waste can happen at any point in the food supply chain, the factors that influence consumer intention has been identified as the main contributors to food waste generation. The main purpose of the research is to develop a conceptual model for the study and to investigate the factors that influence consumers' intentions toward reducing food waste behaviour in restaurants based on recognized consumer behaviour theories and an extensive literature review. Design: This research work is based on secondary sources which are collected from academic journals, newspapers, case studies, and internet searches. Postulates and the influencing variables to consumers' intention to mitigate food waste in restaurants are developed using the focus group interaction. Findings: The study explores the postulates affecting consumers' intention to reduce food waste in restaurants by extensively reviewing empirical theories. Through the development of a conceptual model evaluation, the factors associated with the study were awareness, food quality, environmental concern, attitude, and subjective norms system, which impact consumers' behavioural intention toward food waste mitigation in restaurants. Originality: As the conceptual model was being developed, the research study identifies several postulates with the assistance of several models and theories related to consumer behavioural intention and discusses several factors that influence consumer intention in mitigating food waste in restaurants. Paper Type: Review of literature for the development of the conceptual framework.